حوكمة تقنية المعلومات للحد من المخاطر السيبرانية وتعزيز أمن المعلومات المحاسبية في المؤسسات الليبية العامة (Journal of Academic Research, 2024)
The study aimed to propose a model for information technology governance to reduce cyber risks and enhance the security of accounting information in Libyan public institutions. The study followed the descriptive analytical approach by reviewing studies, reports, models and best practices. The study concluded that information technology governance has a positive role in reducing cyber risks and enhancing the security of accounting information. The most important pillars of the proposed model were: governance, the IT Governance Committee and its mechanisms, and the independence of the internal auditor, with an emphasis on risk management, continuously monitor, transparency and accountability. The study recommended the need for Libyan public institutions to adopt governance and IT governance.